Penelitian Tentang LinkedIn - Lisa Darmayanti; Putri Charolina Barus; Kartini Kartini (Universitas Muhammadiyah Enrekang, 2022)
Article Title. the use of communication tools used by the public so that not everyone understands about the application and running the application, one of which is whatsapp, here the author will discuss about whatsapp, this WhatsApp application is not only used by the general public for communication but is used by librarians also in circulation services as a communication tool about lending and collection to find learning resources needed in activities Learning. The purpose of this study is so that the function or use of the whatsapp application is widely known and developed in terms of features and functionalities.the type used is in the form of qualitative research, using a Narrative study approach. this approach could be defined as a study that focuses on narratives, stories, or descriptions of things related to human experience. WhatsApp is a cross-platform mobile messaging application that allows its users to exchange